2013
DOI: 10.1007/s11165-013-9352-3
|View full text |Cite
|
Sign up to set email alerts
|

Scientists Reflect on Why They Chose to Study Science

Abstract: A concern commonly raised in the literature and in the media relates to the declining proportions of students who enter and remain in the "science pipeline," and whether many countries, including Australia and New Zealand, have enough budding scientists to fill research and industry positions in the coming years. In addition, there is concern that insufficient numbers of students continue in science to ensure an informed, scientifically literate citizenry. The aim of the research presented in this paper was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…The positive influence of the attitude towards research on the intention to enter a research-oriented career is in line with our hypothesis. Venville et al (2013) observed the same, but more specifically for science students. Nevertheless, it is clear that not all variables contribute equally to a better prediction of openness for research.…”
Section: Journal Of Education and Trainingsupporting
confidence: 56%
See 1 more Smart Citation
“…The positive influence of the attitude towards research on the intention to enter a research-oriented career is in line with our hypothesis. Venville et al (2013) observed the same, but more specifically for science students. Nevertheless, it is clear that not all variables contribute equally to a better prediction of openness for research.…”
Section: Journal Of Education and Trainingsupporting
confidence: 56%
“…Several researchers have observed a positive relationship between attitude towards science and choosing an academic education in science among students (Venville, Rennie, Hanbury & Longnecker, 2013). Guerin, Jayatilaka and Ranasinghe (2015) call this intrinsic motivation and saw it as a strong motivator among Australian students to pursue a higher degree by research.…”
Section: Variables and Hypothesesmentioning
confidence: 99%
“…Concurrently, while many graduates and scientists have believed that they always had an interest in science, almost a third of a sample of scientists from the USA (Maltese and Tai 2010;Maltese et al 2014) and over half of a sample from across Australia and New Zealand (Venville et al 2013) have reported that their interest developed during secondary school, which highlights the importance of this time.…”
Section: Children's Aspirations During Secondary Schoolmentioning
confidence: 99%
“…Studies examining some specific PsyCaps for studying science are relatively common in the science education literature. Interest and confidence are the most influential PsyCaps in choosing to study science, according to students (Venville, Rennie, Hanbury, & Longnecker, 2013). Biology interest predicts school student biology career orientations (Uitto, 2014).…”
Section: Defining Capitals In Student Science Choicesmentioning
confidence: 99%